Islamic Sharia and Non-Muslim Citizens in Kanunname During Sultan Abdul Hamid II of the Ottoman Empire - Alizar, Meirison; Muhammadi, Qasim (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
The tolerant spirit of Islam has inspired Ottoman rulers to adopt policies relating to non-Muslim citizens. The leadership crisis in the Ottoman Empire and the Western interests through capitulation have changed judicial system in the empire, including the system for non-Muslims that allows them to conduct their own judiciary and provide absolute freedom of religious matters. Tanzim?t, which is expected to bring improvements to the legislation system in Ottoman Empire, has marginalized Islamic law which is only enforced in a?w?l al-shakh?iyyah. Sultan Abdul Hamid II tried to maintain Islamic law by codifying Western European style. Some legal codifications contain qaw?id fiqhiyyah (principles of Islamic law) which are sourced from the books of the Hanafi School of jurisprudence, and some others adopt Western laws by taking a few opinions of Islamic jurisprudence. This study analyzed various literatures related to policies towards non-Muslim citizens in the Ottoman era. The study uses descriptive and qualitative methods with a content analysis approach. Broadly speaking, this study found that the Ottoman Empire had given good treatment to non-Muslim citizens. The non-Muslim citizens get various facilities from the State, including the establishment of special institutions that handle their own affairs, although at the same time they have been used by Western countries to support their interests in Ottoman Empire.